TOWARDS SCHOOL HEADS' EVALUATION ON FILIPINO ENGLISH TEACHERS' CLASSROOM PERFORMANCE - Magna Susada Sejismundo; Renalyn C. Estiller (PUPIL: International Journal of Teaching, Education and Learning, 2026)
This study examined school heads’ evaluation of Filipino English teachers’ classroom performance, focusing on instructional strategies, assessment for learning, learner engagement, and professional conduct. The study was grounded on Danielson’s Framework for Teaching and Stronge’s Teacher Evaluation Model to determine the consistency and developmental value of current evaluation practices. A quantitative descriptive design was employed, involving school heads and Filipino English teachers from selected schools. Data were collected through standardized evaluation instruments and analyzed to identify performance trends and variations in evaluation practices. Findings revealed that teachers demonstrated strong pedagogical competence and professional conduct, especially in lesson organization, subject mastery, and ethical behavior. However, inconsistencies were noted in the effective use of formative assessments and in sustaining learner engagement. Evaluation practices were found to be more compliance-oriented, with limited use of structured post-observation feedback. The study concludes that a unified, competency-based evaluation framework is needed to strengthen reliability, fairness, and instructional improvement. Enhancing school heads’ supervisory competencies and improving teachers’ assessment literacy are essential to advancing English language teaching performance.